Unified molecular approach for spatial epigenome, transcriptome, and cell lineages - Yung-Hsin Huang; Julia A. Belk; Ruochi Zhang; Natasha E. Weiser; Zachary Chiang; Matthew G. Jones; Paul S. Mischel; Jason D. Buenrostro; Howard Y. Chang (Proceedings of the National Academy of Sciences, 2025)
Spatial epigenomics and multiomics can provide fine-grained insights into cellular states but their widespread adoption is limited by the requirement for bespoke slides and capture chemistries for each data modality. Here, we present SPatial assay for Accessible chromatin, Cell lineages, and gene Expression with sequencing (SPACE-seq), a method that utilizes polyadenine-tailed epigenomic libraries to enable facile spatial multiomics using standard whole transcriptome reagents. Applying SPACE-seq to a human glioblastoma specimen, we reveal the state of the tumor microenvironment, extrachromosomal DNA copy numbers, and identify putative mitochondrial DNA variants.